Peranan Kelompok Tani Dalam Meningkatkan Produksi Usahatani Kedelai di Desa Bulu Tellue Kecamatan Tondong Tallasa Kabupaten Pangkep - Harnisa Harnisa; Abd. Asis Pata; Azisah Azisah (Universitas Muslim Maros, 2021)
This research was conducted in Pangkep Regency, South Sulawesi. This location was chosen with the consideration that it has long been managing the data used, namely: secondary data, namely data obtained from agencies / institutions related to or related to this research. The purpose of this study was to determine the role of farmer groups in increasing soybean farming production in the village of Bulu Tellue, Tondong Tallasa District, Pangkep Regency. The collected data is then tabulated to obtain real data used for analysis purposes. This study used a quantitative descriptive analysis method to determine the size of the production obtained from the role of farmer groups in increasing soybean farming in Bulu tellue village. The results of the research can be seen that the average amount of production obtained by farmers is 45, 640 and the productivity results obtained are 273.87.